Pilot scale evaluation of thin film composite membranes for reducing wastewater volumes: osmotic concentration process - Abdelrahman M. Awad (16932519) (2023)
Gas operations generate large volumes of wastewater, necessitating efficient water management schemes. This study evaluates a forward osmosis (FO) pilot plant for volumes reduction of gas industry process water (PW). The osmotic pressure difference between seawater (40 g/L Total Dissolved Solids (TDS)) and low salinity (2 g/L TDS) PW is used for the osmotic concentration (OC). In the OC, PW volumes get reduced, while diluted draw solution (DS) is directly discharged, obviating the high-energy DS recovery step. A thin-film composite hollow fiber (HF) FO membrane was tested under FO mode using synthetic solutions to assess the performance on the OC unit. Subsequently, the pilot unit was subjected to PW feed for 48 h of continuous operation, primarily to evaluate water flux, reverse solute flux (RSF), and membrane fouling. The cleaning requirement to remove contaminants from the membrane surface was examined. The membrane achieved a water flux and RSF between 11.5 to 6.43 LMH and 38.57 to 9.45 mmol h−1 m−2, respectively at feed recovery rates between 60 and 90%. The membrane achieved a water flux of 10 LMH, which slightly decreased to 9.6 after 48 h of operation, mainly due to inorganic scaling. Lastly, cleaning with citric acid succeeded in recovering the initial water flux. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-023-00495-y